Technology and education issues in administration, policy, and applications in K12 schools - Hunter, Richard C.; Tettegah, Sharon Y. (Elsevier JAI, 2006)
In today's society where most students own MP3 players, engage in constant instant messaging and downloading from the Internet, more than ever school administrators and staff should be aware of issues in administration, policy, and applications. This book provides a comprehensive presentation of current policies and practices of technology in K12 schools. The first part of the book lays out the foundation of what schools should be concerned about involving various aspects of technology and its impact on school administration and teaching. The second part of the book introduces technology, policy and philosophical discussions on the use of technology in schools. The third section of the book provides an examination of technology of practical applications of technology currently used in schools. Sharon Tettegah holds faculty appointments in the Department of Curriculum and Instruction and Educational Psychology. She also has appointments with the National Center for Supercomputing Applications and the Beckman Institute at the University of Illinois, Urbana Champaign. Richard C. Hunter is a faculty member, and former chair in the Department of Educational Organization and Leadership in the College of Education at the University of Illinois, Urbana Champaign.